2017
DOI: 10.1016/j.edurev.2017.10.001
|View full text |Cite
|
Sign up to set email alerts
|

An integrative review of the cognitive costs and benefits of note-taking

Abstract: List of most important changes made:-Definition of research aim and research questions in the Introduction.-Explanation of the origination of the analytic criteria in the description of the literature review. -Shortening of the sections on lecture speed, individual differences, and type of questions.-Addition/rewriting of concluding paragraph for lecture speed, structure of lecture material, note-taking style, and structure of note-taking. -Inclusion of several recent articles: Svinicki (2017), Reed, Rimel, an… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
54
1
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(58 citation statements)
references
References 48 publications
1
54
1
2
Order By: Relevance
“…Not only that, lecture recordings can be seized as an opportunity to promote effective note-taking and it is important to integrate recording usage with other, more traditional study behaviours. Producing notes whilst listening to a lecture is a dual task, in which cognitive resources need to be allocated to either listening to the instructor or to writing down notes (Jansen et al, 2017). Thus, considerable cognitive resources need to be expended to create useful notes and lecture recordings can support better note-taking.…”
Section: Take Effective Notes During Lectures For Later Use With Lectmentioning
confidence: 99%
“…Not only that, lecture recordings can be seized as an opportunity to promote effective note-taking and it is important to integrate recording usage with other, more traditional study behaviours. Producing notes whilst listening to a lecture is a dual task, in which cognitive resources need to be allocated to either listening to the instructor or to writing down notes (Jansen et al, 2017). Thus, considerable cognitive resources need to be expended to create useful notes and lecture recordings can support better note-taking.…”
Section: Take Effective Notes During Lectures For Later Use With Lectmentioning
confidence: 99%
“…Prior to reengaging with this 'first pass' of information, I assumed it to be a relatively 'pure' documentation of the workshop content. Discovering embodied reflections within my notes was unexpected, despite this kind of cognitive processing being common in high quality notetaking (Jansen et al, 2017). In previous discussions of the reflective doodling process I have failed to recognise this aspect of notetaking as reflection in action.…”
Section: Drawing As Part Of Reflectionmentioning
confidence: 89%
“…Wang et al (2017) showed that taking notes can help learners shield against distractions from irrelevant information. With auxiliary note‐taking supports to prevent distraction, the Two Low WMC could also benefit from the external store function (Lin et al, 2016; Makany et al, 2009) and the encoding effect to process information to a deeper level, as suggested by Jansen et al (2017). Thus, the current study provides further support for the claim that note‐taking may help learners with low WMC during their online search.…”
Section: Discussionmentioning
confidence: 99%
“…2.2 | The effect of note-taking in general and in the context of online search performance Note-taking serves as an external store of memory to hold information and facilitate cognitive processing to avoid mental overload (Lin, Lee, Wang, & Lin, 2016;Makany, Kemp, & Dror, 2009). Besides, notetaking can help learners focus on encoding information for a deeper level of processing that enhances learning (Jansen, Lakens, & IJsselsteijn, 2017).…”
Section: Online Search and Multitasking: Influence Of Working-memormentioning
confidence: 99%